The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1377/hlthaff.2008.0701
|View full text |Cite
|
Sign up to set email alerts
|

Greater Use Of Preventive Services In U.S. Health Care Could Save Lives At Little Or No Cost

Abstract: There is broad debate over whether preventive health services save money or represent a good investment. This paper analyzes the estimated cost of adopting a package of twenty proven preventive services-including tobacco cessation screening, alcohol abuse screening, and daily aspirin use-against the estimated savings that could be generated. We find that greater use of proven clinical preventive services in the United States could avert the loss of more than two million lifeyears annually. What's more, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(170 citation statements)
references
References 11 publications
2
161
0
1
Order By: Relevance
“…Timely implementation of breast cancer screening services not only averts a loss of significant number of life years, but also reduces a considerable burden on the health care system (Elixhauser, 1991;Maciosek et al, 2010). Yet, utilization of breast cancer screening services is poor in South Asian women living in Asia (Maqsood et al, 2009;Bhatt et al, 2011;Grosse Frie et al, 2013), the US (Islam et al, 2006;Glenn et al, 2009;Lee et al, 2010) as well as other western countries (Sutton et al, 2001;Szczepura et al, 2008;Price et al, 2010;Rajan et al, 2011;Peltzer and Phaswana-Mafuya, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Timely implementation of breast cancer screening services not only averts a loss of significant number of life years, but also reduces a considerable burden on the health care system (Elixhauser, 1991;Maciosek et al, 2010). Yet, utilization of breast cancer screening services is poor in South Asian women living in Asia (Maqsood et al, 2009;Bhatt et al, 2011;Grosse Frie et al, 2013), the US (Islam et al, 2006;Glenn et al, 2009;Lee et al, 2010) as well as other western countries (Sutton et al, 2001;Szczepura et al, 2008;Price et al, 2010;Rajan et al, 2011;Peltzer and Phaswana-Mafuya, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…18 A study of the likely cost-effectiveness of a package of 20 preventive services (including all of the services measured in this study) found that, if uptake reached 90 percent, it could avert the loss of more than 2 million life-years and save $3.7 billion annually. 19 The ACA will not solve all the problems with access to care for previously uninsured individuals. Even with the ACA, the United States will continue to have a substantial number of uninsured people, and although the ACA includes provisions to increase access to preventive care, these provisions do not apply to the uninsured.…”
Section: Discussionmentioning
confidence: 99%
“…25 Such an imbalance defies peer-reviewed findings that show prevention activities in most instances are far more costeffective in improving health than medical treatment. 25,26 Unlike medical schools, SPH do not receive core federal funding for education [beyond a small pool of students], such as is received through Medicare funding for medical residents or core federal funding for research and service/care available through the Veterans Administration for faculty effort.…”
Section: Sources Of Support For Sphmentioning
confidence: 99%